An analysis of the essential medicines policy in primary care: Findings from MedMinas project - Luz, Tatiana Chama Borges; Tavares, Noemia Urruth Leão; Marques, Isabela Cristina; de Castro, Ana Karine Sarvel; Cota, Betania Barros (Frontiers in Pharmacology, 2022)
Background: Essential Medicines Policy (EMP) has been adopted in Brazil to improve the provision and use of pharmaceuticals. This mixed methods study aims to bring real-world evidence of the EMP implemented in municipalities in the context of primary care in Minas Gerais (20,997,560 inhabitants), Southeast Brazil. Methods: We analysed the core output of the EMP, i.e., the municipal essential medicines lists (MEML) and the effects of the policy on the procurement and availability of medicines. Data sources included a sample of 1019 individuals (patients, health managers and health professionals), 995 prescriptions, 2365 dispensed medicines and policy documents from 26 municipalities. Data were collected between April and October 2019. Document analysis and thematic content analysis were performed, and four availability indexes were estimated. Results: The findings suggest an overall lack of standardised and methodologically sound procedures to elaborate the MEML. Funding and public purchasing processes were found to be the major obstacles to medicine procurement. Only 63% of medicines were available at public community pharmacies and just 46.2% of patients had full access to their pharmaceutical treatment. Conclusion: This study reveals weaknesses in the implementation of EMP and a clear disconnection between medicines selection, procurement, and availability, the three core elements of the supply system. These findings contribute to informing future policy improvement actions to strengthen this system. Other countries aiming to advance towards universal health coverage may learn from the challenges that primary care in Brazil still needs to address.